PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) DENGAN PEMBERIAN BERBAGAI JENIS PUPUK ORGANIK - Purwanto, Ruli Joko; Syafrullah, Syafrullah; Astuti, Dessy Tri; Safrudin, Adi (Universitas Muhammadiyah Palembang, 2021)
The use of organic fertilizers on plants is not only useful for increasing soil fertility while increasing plant growth and productivity, organic fertilizers also have relatively cheap prices. This research aims to determine the right type of organic fertilizer on the growth and production of sweet corn (Zea mays saccharata Sturt).The research was conducted from May to July 2019 in Srimenanti Village, Tanjung LagoSub District, Banyuasin District, South Sumatra Province.The research method used a completely block randomized design (CBRD) with 5 treatments and 5 replications. The results of the analysis of diversity showed that the treatment of the type of organic fertilizer had a very significant effect on the number of leaves, but had no significant effect on the other observed variables. Baraplus organic fertilizer provides the highest number of leaves.